2013
DOI: 10.3892/ijmm.2013.1346
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus supernatant induces the release of mouse β-defensin-14 from osteoblasts via the p38 MAPK and NF-κB pathways

Abstract: Mammalian β-defensins are small cationic peptides of approximately 2-6 kDa that have been implicated in mediating innate immune defenses against microbial infection. Previous studies have reported that mouse β-defensin-14 (MBD‑14), based on structural and functional similarities, appears to be an ortholog of human β-defensin-3 (HBD-3). The aim of this study was to identify the signaling pathways that contribute to the expression of MBD-14 in mouse osteoblasts (OBs) upon contact with methicillin-resistant Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Our recent studies identified that when mouse osteoblasts contacted with MRSA supernatant, the relevant activated signaling pathway p38 mitogen-activated protein kinase could contribute to the obvious release of MBD-14, which is the structural and functional ortholog of HBD-3 [43,44]. Meanwhile, we also indicated the potential role of increasing the release of MBD-14 in the treatment of osteomyelitis in mice [22,45]. In addition to their role of local high Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Our recent studies identified that when mouse osteoblasts contacted with MRSA supernatant, the relevant activated signaling pathway p38 mitogen-activated protein kinase could contribute to the obvious release of MBD-14, which is the structural and functional ortholog of HBD-3 [43,44]. Meanwhile, we also indicated the potential role of increasing the release of MBD-14 in the treatment of osteomyelitis in mice [22,45]. In addition to their role of local high Fig.…”
Section: Discussionmentioning
confidence: 83%
“…There are total 82 DEGs involved in MAPK signal pathway and 45 DEGs in NF-κB signaling. NF-κB and MAPK signaling play important roles in defense responses against bacterial infection by regulating production of cytokines, such as Enterococcus faecalis, S. aureus , and M. tuberculosis (Zhu et al, 2013; Deng et al, 2014; Zou and Shankar, 2015). Thus, the NF-κB and MAPK signaling may also have the critical importance during P. multocida infection.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus cells treated with recombinant mBD-3 showed growth inhibition and morphological and structural changes, including delamination and perforation of the peripheral cell walls, porosity, and release of the cytoplasmic contents (22,23). mBD-14 is expressed in a wide variety of tissues, including spleen, colon, and tissues of the upper and lower respiratory tract (24), is induced in osteoblasts upon stimulation with S. aureus supernatants, and exhibits antistaphylococcal activity (25).…”
mentioning
confidence: 99%